Effects of The Inclusion of Star Gooseberry Dried Leaf Extract in Ration on Egg Organoleptic Values of Local Duck - Anggraeni; Ristika Handarini; Deden Sudrajat; Burhanudin Malik; Viona Oktavia (Universitas Djuanda, 2021)
Duck egg is known to have an unpleasant fishy odor which often becomes a factor reducing its acceptance in public. This odor is resulted from lipid oxidation which can be avoided by using an antioxidant. This study was aimed at assessing the effects of the inclusion of star gooseberry (Sauropus androgynus) dried leaf extract in ration on egg organoleptic quality of local duck. The study was conducted in a completely randomized design with 4 treatments and 4 replicates. Sensory test by 60 semi-trained panelists and hedonic quality and hedonic tests were conducted. Data were subjected to a Kruskal-Wallis test. Results showed that treatments gave significant effects (P <0.05) on aroma (hedonic), yolk color, and aroma (hedonic quality). It was concluded that the inclusion of star gooseberry dried leaf extract by 1,5% in ration improved the quality of egg yolk color, egg aroma, and consumers’ preference. A further study on the effects of DSGLE on meat quality and protein digestibility in ducks was recommended.